(untitled) (Biological Sciences - PJSIR, 2007)
Ph ysical an d chemi cal ch aracteristics i ncl ud i ng fatty aci d composition of sam ples of seven commercially avai l abl e Nige l/ a saliva oi l and three fresh l y extracted seed oi l , collected from di fferent l oca l i ti es, were determi ned by gas liq u id chromatography. The average and standard deviat ion s foun d were: refracti ve i ndex at 20 °C, 1 .473 ± 0.001 8; speci fic grav i ty a t 20 °C, 0.91 66 ± 0.0002 ; iod i ne va l ue (I V, Wij ’s), 1 1 9.98 ± 1.8; saponification va l u e, 201.80 ± 2 .2 and un saponifi able matter, 0.6 1 % ± 0.05. Fatty acid (FA) profi l e was based on h i gh level s of un satu rated FA l i ke ol e i c acid, 24 . 1 7% ± 0.6 I ; l i n ole i c acid, 53.64% ± 0.799 and eicosadienoic aci d, 2.3% ± 0.37. Saturated FA su ch as pa l mi tic acid and stearic acid amounted to 1 4.82% ± 0.49 an d 2.95% ± 0.37, respecti vely. Myristic and pa l mi toleic acids we re also detected i n mi nor quanti ty.